Development and pilot testing of a novel behavioral intervention for adults with type 2 diabetes using intervention mapping. Issue 1 (1st January 2017) - Miller, Carla K.; Pawelczyk, Katlyn; Cheavens, Jennifer S.; Fujita, Kentaro; Moss, Sara
ABSTRACT: Purpose: A healthy diet and consistent physical activity (PA) form the foundation for effective self-management in adults with type 2 diabetes mellitus (T2DM). Behavioral interventions, which target diet and PA, can facilitate effective diabetes self-management practices. Greater clarity regarding the 'active ingredients' incorporated into behavioral interventions is needed to inform the evidence base about effective intervention techniques to advance behavioral theories and to improve clinical practice. The use of intervention mapping (IM) to develop a novel diabetes intervention to increase consumption of low glycemic index (GI) foods and to increase moderate-to-vigorous intensity PA is presented. Methods: Determinants from self-regulation and the Health Action Process Approach theoretical framework formed the foundation of the intervention. The IM taxonomy of behavior change methods and strategies from Hope Therapy (e.g. goal maps) were used to guide techniques for changing selected theoretical determinants of behavior. A pilot study of the intervention among adults with T2DM ( n  = 12) was conducted using a pre-/post-test design to evaluate intervention components and participant acceptability. Results: Participants attended a mean (±SD) of 8 (±1.4) of the 10 weekly 90-minute, group-based sessions. The magnitude of effect was moderate ( d  > 0.50) for the change in behavioral intentions, action control, and action and coping planning for engaging in PA and large ( d  > 0.80) for the change in action self-efficacy and action and coping planning for eating low GI foods post-intervention. Conclusions: Greater emphasis on value-based decision-making, the goal mapping process, and successively progressive exercise goals should be included in future versions of the intervention. Based on pilot testing, a larger randomized controlled trial that incorporates these intervention modifications is warranted and the modified intervention has a greater likelihood for success.